2003
DOI: 10.1108/09685220310500126
|View full text |Cite
|
Sign up to set email alerts
|

Decision support through knowledge management: the role of the artificial intelligence

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…One of the most significant problems is the organization and further distribution of business knowledge [27]. As per the findings of [6,28], it is observed that organizational knowledge has nine basic steps for its management either the explicit, tacit or subjective dimensions. These are transforming the information into knowledge, identification and verification of knowledge, capturing and securing the knowledge, organizing and combining the knowledge, creation and learning of knowledge and finally the distribution and selling of knowledge.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…One of the most significant problems is the organization and further distribution of business knowledge [27]. As per the findings of [6,28], it is observed that organizational knowledge has nine basic steps for its management either the explicit, tacit or subjective dimensions. These are transforming the information into knowledge, identification and verification of knowledge, capturing and securing the knowledge, organizing and combining the knowledge, creation and learning of knowledge and finally the distribution and selling of knowledge.…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, their study is observed a reasonable contribution in the field of big data and KM for AI. In their study [6], have considered the decision support through KM with the role of AI in computer bases system. Authors explain that both decision support and KM are interdependent to each other in various business organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 21st century, AI has become an important area of research in all fields: Engineering, science, education, medicine, business, accounting, finance, marketing, economics, stock market, and law, among others [12][13][14][15][16][17][18]. The range of AI has grown enormously since the intelligence of machines with machine learning capabilities has created profound impacts on business, governments, and society [19].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the decision-making in projects, the knowledge management can be used to take trustworthy decisions in relation to the strategy, competitors, customers, distribution channels and products and services life cycles (DAVENPORT; PRUSAK, 1998). The employment of KM as the support to the decision-making process consists of a subject of innumerable researches (PADMA;BALASUBRAMANIE, 2009;RANTAPUSKA;IHANAINEN, 2008;NICOLAS, 2004;COURTNEY, 2001;METAXIOTIS et al, 2003;HOLSAPPLE, 2001), hence the capacity to make a good decision is very important for the success of a project (AL-HARBI, 2001). Comprehension and response to the risks in a company is a task that depends on the intellectual capital of the company (NEEF, 2005) and one of the most powerful tools in the risk management in projects is knowledge (COOPER, 2003).…”
Section: Knowledge Management and The Decision-making Processmentioning
confidence: 99%